1983
DOI: 10.1111/j.1469-8986.1983.tb03283.x
|View full text |Cite
|
Sign up to set email alerts
|

Event‐Related Potential Correlates of Two Stages of Information Processing in Physical and Semantic Discrimination Tasks

Abstract: Event‐related potentials were studied while subjects performed physical and semantic discrimination tasks. Two negative components, NA and N2, were observed in both kinds of discriminations. The earlier component, NA, had a constant onset latency, but its peak latency varied as a function of stimulus complexity. N2 latency varied in relation to changes in the peak of NA. RT and P3 followed N2 by similar amounts of time across tasks. The NA and N2 components were interpreted as reflecting partially overlapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
3
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(141 citation statements)
references
References 38 publications
6
131
3
1
Order By: Relevance
“…Semantic-based compatibility tasks produce a larger P300 latency/response time difference compared to spatial compatibility tasks. Furthermore, P300 latency has been used as a metric for timing mental events producing other ERP components (Renault et al, 1982;Ritter et al, 1983). Inferences based on component timing and behavioral output therefore must take into account the type of stimulus and decision process underlying response activation (Pfefferbaum et al, 1986;Renault, 1981, 1985).…”
Section: P300 Latencymentioning
confidence: 99%
“…Semantic-based compatibility tasks produce a larger P300 latency/response time difference compared to spatial compatibility tasks. Furthermore, P300 latency has been used as a metric for timing mental events producing other ERP components (Renault et al, 1982;Ritter et al, 1983). Inferences based on component timing and behavioral output therefore must take into account the type of stimulus and decision process underlying response activation (Pfefferbaum et al, 1986;Renault, 1981, 1985).…”
Section: P300 Latencymentioning
confidence: 99%
“…Of this total mean RT, an average of 200 ms was allocated to the residual term (i.e., peripheral sensory and motor processes; μ R = 200 ms), and a Ee further 100 ms each was allocated to the sensory and motor processes whose durations would be influenced by G (i.e., stages A and C, respectively). Various psychophysiological evidence suggests that totals of approximately 200 ms each would be realistic values for the total durations of the sensory and motor stages (e.g., Carbonnell, Hasbroucq, Grapperon, & Vidal, 2004;Hillyard & Anllo-Vento, 1998;Ritter, Simson, & Vaughan, 1983). The remaining 200 ms was allocated to the central stage B, which also seems plausible for straightforward choice RT tasks with arbitrary stimulus-response mappings.…”
Section: Appendix 3 Assumptions and Parameter Values Used To Illustramentioning
confidence: 99%
“…The present study showed that the visual N2 latency was delayed in patients with multiple lacunar infarcts. In addition, the delay of visual N2 was not due to a delay of the preceding NA, although NAis known to occur in the latency range of the N2 peak of the ERP (8,9). NAand N2 reflect sequential stages of information processing, namely, pattern recognition and stimulus classification (8).…”
Section: Discussionmentioning
confidence: 97%
“…Figure 1 shows an example of the ERPwave forms in a normal subject. NAand N2 were elicited according to the method reported by Ritter et al (8,9). To more clearly delineate N2, the ERPs to the frequent stimuli were subtracted from those to the infrequent stimuli for each subject in each discrimination tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation